Penggunaan Variasi Bahasa “Slang” pada Kolom Komentar di Platform Media Sosial Youtube @Deddy Corbuzier & @Denny Sumargo : Kajian Sosiolinguistik - Nurmaini; Fikri, Hasnul; Syofiani, Syofiani; Naini, Ineng; Morelent, Yetty (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Language serves as a symbolic system used by humans to communicate, express thoughts and emotions, and convey information. In the era of digital technology, social media has become an interactive space that fosters the emergence and development of new forms of language, one of which is slang. This study aims to describe the forms, functions, and meanings of slang variations found in the comment sections of YouTube channels owned by @DeddyCorbuzier and @DennySumargo. The research employs a descriptive qualitative method, using documentation and observation techniques to collect user comments from January 1 to March 31, 2025. The findings reveal that the forms of slang identified include acronyms, abbreviations, phonetic spellings, borrowings from foreign languages, and the creation of new lexical items. The primary functions of slang use involve emotional expression, social critique, group identity markers, and communicative efficiency. Semantically, slang often undergoes symbolic shifts or takes on metaphorical meanings, depending on the user's social context. Slang in social media reflects the dynamic nature of language and embodies the identity and cultural practices of digital communitie